Analisis Kemampuan Representasi Matematis pada Materi Barisan dan Deret Berdasarkan Gaya Belajar - Baiq Rachmawatin Ramadhana; Sudi Prayitno; Nourma Pramestie Wulandari; Sri Subarinah (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2022)
This study aims to describe the mathematical representation ability based on the learning styles of students for 11th grade of senior high school 4 Praya Academic year 2020/2021. Type of research used descriptive research with a quantitative approach. In determining the sample used purposive sampling technique. The sample in this study was 60 students of class XII MIPA 4 and XII MIPA 6 SMAN 4 Praya. According results of the research, the conclusion was mathematical representation ability of students with visual learning style reach 51.59 in very low category. The mathematical representation ability of students with auditory learning style reach 64.29 in medium category. The mathematical representation ability of students with kinesthetic learning styles reach 49.89 in very low category. The mathematical representation ability of students with auditory learning style has highest category than students with visual and kinesthetic learning styles.